2020
DOI: 10.1007/s00415-020-09983-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of alemtuzumab in patients with RRMS: 12-year follow-up of CAMMS223

Abstract: Background In the phase 2 CAMMS223 trial (NCT00050778), alemtuzumab significantly improved clinical and MRI outcomes versus subcutaneous interferon beta-1a over 3 years in treatment-naive patients with relapsing–remitting MS. Here, we assess efficacy and safety of alemtuzumab over 12 years in CAMMS223 patients who enrolled in the CAMMS03409 extension (NCT00930553), with available follow-up through the subsequent TOPAZ extension (NCT02255656). Methods In CAMMS223, patients received 2 alemtuzumab courses (12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…That might cause a selection bias in favor of patients with positively experiences of alemtuzumab, as patient participation in the extension study was voluntary. 47 Nevertheless, the study confirmed the efficacy and safety of alemtuzumab on long-term follow-up.…”
Section: Alemtuzumab In Clinical Trials On Msmentioning
confidence: 61%
“…That might cause a selection bias in favor of patients with positively experiences of alemtuzumab, as patient participation in the extension study was voluntary. 47 Nevertheless, the study confirmed the efficacy and safety of alemtuzumab on long-term follow-up.…”
Section: Alemtuzumab In Clinical Trials On Msmentioning
confidence: 61%
“…The highest risk of serious infectious complications with alemtuzumab use in patients with multiple sclerosis was reported to be the first year of treatment (3.3%/year). 87 In the same study, it was observed that the incidence of serious infections decreased in the long term (0.8%/year) in patients with 12-year follow-up. An analysis of 399 patients receiving different treatments for multiple sclerosis (including alemtuzumab) indicated that COVID-19 incidence and disease course were similar to those in the normal population.…”
Section: Introductionmentioning
confidence: 84%
“…The 12-year long-term outcomes of alemtuzumab use in multiple sclerosis patients were recently published. 87 Its efficacy has been demonstrated both clinically and on magnetic resonance imaging. There are case reports related to its use in the treatment of uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Three randomized, rater-blinded clinical trials assessing the efficacy of alemtuzumab in MS treatment, using an effective comparator drug, have been performed: CAMMS223 (9), CARE-MS I (10), and CARE-MS II (11). In sum, alemtuzumab significantly reduced clinical and radiological disease activity and slowed down progression of relapsing-remitting MS (RRMS) to secondary progressive MS, also in the long-term and in patients with highly active disease (HAD) (4,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%